2018
DOI: 10.3390/vaccines6020020
|View full text |Cite
|
Sign up to set email alerts
|

New Kids on the Block: RNA-Based Influenza Virus Vaccines

Abstract: RNA-based immunization strategies have emerged as promising alternatives to conventional vaccine approaches. A substantial body of published work demonstrates that RNA vaccines can elicit potent, protective immune responses against various pathogens. Consonant with its huge impact on public health, influenza virus is one of the best studied targets of RNA vaccine research. Currently licensed influenza vaccines show variable levels of protection against seasonal influenza virus strains but are inadequate agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 69 publications
0
65
0
4
Order By: Relevance
“…The capability of RNA vaccines to trigger strong, protective immune responses against a wide spectrum of pathogens has led to a large number of studies focusing on the use of these vaccines against influenza virus. As recently approved influenza vaccines demonstrated variable and inadequate protection, a promising efficacy has been shown for several more recently RNA vaccines types in preclinical models …”
Section: Influenza Rna Vaccinementioning
confidence: 99%
See 2 more Smart Citations
“…The capability of RNA vaccines to trigger strong, protective immune responses against a wide spectrum of pathogens has led to a large number of studies focusing on the use of these vaccines against influenza virus. As recently approved influenza vaccines demonstrated variable and inadequate protection, a promising efficacy has been shown for several more recently RNA vaccines types in preclinical models …”
Section: Influenza Rna Vaccinementioning
confidence: 99%
“…Single‐stranded oligoribonucleotides and the products of their degradation are recognized by the endosomal sensors Toll‐like receptor 7 (TLR7) and TLR8, leading to type I interferon production . In addition, trivalent saRNA (small activating RNAs) vaccination could result in anti‐H1N1 and H3N2 IgG responses …”
Section: Influenza Rna Vaccinementioning
confidence: 99%
See 1 more Smart Citation
“…The two main types of RNA vaccines used against influenza viruses are self-amplified mRNA (SAM) vaccine and nonreplicating mRNA vaccine. A pioneering work showed that intramuscular injection of SAM encoding the HA gene in A/California/07/2009, combined with oil-in-water nanoemulsions, could protect mice and ferrets from homologous and heterogeneous influenza viruses [4,14]. Barr and colleagues provided evidence that a single intradermal immunization with a 10-µg mRNA vaccine encoding the nucleoside-modified HA gene of H10N8 or H7N9 led to the production of HA antibodies in mice for more than a year.…”
Section: Introductionmentioning
confidence: 99%
“…Barr and colleagues provided evidence that a single intradermal immunization with a 10-µg mRNA vaccine encoding the nucleoside-modified HA gene of H10N8 or H7N9 led to the production of HA antibodies in mice for more than a year. Phase I clinical trials (NCT03076385) using this platform were launched due to promising preclinical results [14,15].…”
Section: Introductionmentioning
confidence: 99%